2012
DOI: 10.3109/02713683.2012.669005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Diabetic Retinopathy in Subjects with Suboptimal Glycemic, Blood Pressure and Lipid Control. Sankara Nethralaya Diabetic Retinopathy Epidemiology and Molecular Genetic Study (SN-DREAMS, Report 33)

Abstract: We found high prevalence of suboptimal metabolic control among subjects with type 2 diabetes. Suboptimal glycemic and SBP control, and their combination was the most detrimental for the development of DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
3
15
1
3
Order By: Relevance
“…In the MDRS 24-month cohort study, lower hemoglobin was associated with the presence of STDR at baseline (previously reported 14 ) but not with the progression of DR. Cross-sectional (but not cohort) studies have demonstrated an association between the presence of DR and anemia in India32, 33, 34 and China 35 . Potential confounders of the association between hemoglobin and retinopathy are socioeconomic and nutritional status and decreased erythropoietin production due to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In the MDRS 24-month cohort study, lower hemoglobin was associated with the presence of STDR at baseline (previously reported 14 ) but not with the progression of DR. Cross-sectional (but not cohort) studies have demonstrated an association between the presence of DR and anemia in India32, 33, 34 and China 35 . Potential confounders of the association between hemoglobin and retinopathy are socioeconomic and nutritional status and decreased erythropoietin production due to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[17] The inter-study discrepancy could be explained by differences in study design (e.g. population-based vs. clinical), and study population (Indian[17] and Israeli[24] participants).…”
Section: Discussionmentioning
confidence: 99%
“…[17] The inter-study discrepancy could be explained by differences in study design (e.g. population-based vs. clinical), and study population (Indian[17] and Israeli[24] participants). Similarly, definitions of the indicators of diabetes control varied, particularly for poor lipid control, which was defined as TC:HDL≥4.0 in our study, and LDL≥100mg/dl[17, 24] and TC≥5.5 mmol/l[25] in the others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4344] Cognitive functions have been affected by DM especially in older patients with long standing DM. Hence, to prevent and minimize these unwanted disease effects, TGC is recommended.…”
Section: Glycemic Controlmentioning
confidence: 99%